Twin Prime Number Theorem (Global Journal of Science Frontier Research, 2017)
Let Pt N be the number of twin primes less than or equal to N Pi 3 Pi Pm be taken over the odd primes less than or equal to N then exists the formula as follows Pt N INT N 1 1 2 1 2 Pi 2 INT Ct 2N Ln N 2 2 Pt N INT 0 660 2N Ln N 2 2 0 660 2N Ln N 2 3 Pi Pi 2 Pi 1 2 Ct 0 6601618158 Where the INT expresses the taking integer operation of formula spread out type in
Keywords: twin prime; bilateral sieve method